Comprehensive Chloroplast Genome Analysis of Four Callitriche (Plantaginaceae) Species for Phylogenetic and Conservation Insights - Zirui Zhang; Wenbo Shi; Siqi Hu; Lanruo Mou; Chao Shi; Bingyue Zhu; Jing Yang (Horticulturae)
Callitriche species are capable of purifying water, promoting wetland restoration, and providing natural shelters. Moreover, they can be utilized as horticultural plants for landscape greening. However, due to the threats of climate change and environmental degradation, some species within this genus have been listed as endangered. This study utilizes chloroplast genome analysis to provide molecular evidence for the classification and conservation of these species. We conducted a comprehensive sequencing and characterization of the complete chloroplast genomes of four species within the genus Callitriche: C. cophocarpa, C. hermaphroditica, C. palustris, and C. stagnalis. The genome sizes ranged from 150,042 to 150,879 bp, with a GC content of 37.5–37.8% and between 131 and 132 genes. Comparative genomic analysis revealed several highly variable intergenic regions (e.g., rps16–psbK, trnS-GCU–trnG-UCC, ccsA–ndhD, ndhF–rpl32, and trnN-UGG) and the ycf1 gene, highlighting their potential as phylogenetic markers. Phylogenetic analyses confirmed the monophyly of Callitriche and supported C. hermaphroditica as an early-diverging lineage within the genus. Notably, the phylogeny also resolved Hemiphragma and Veronicastrum as sister taxa, contributing insights into evolutionary relationships within Plantaginaceae. This study provides comprehensive chloroplast genomic data for Callitriche, offering valuable molecular markers for phylogenetic research, taxonomic clarification, and conservation of this ecologically significant genus.